Characteristics and Design of Islamic Economy - Budi Jaya Putra; Altis Puspa Gatari (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Islamic economics is an economic system rooted in sharia principles, emphasizing justice, social welfare, and ethical business practices. In recent years, there has been a growing interest in understanding and implementing Islamic economic principles as an alternative to conventional economic systems. Purpose. The primary aim of this research is to design and build a comprehensive Islamic economic framework. By examining both classical and contemporary literature, this study seeks to identify fundamental concepts and practices that define Islamic economics and explore how these can be applied in today's economic environment. Method. The research utilizes a library research method, which involves extensive literature review. Data collection was conducted by searching written sources such as academic books, scholarly journals, articles from online databases, and official documents. Results. The study found that Islamic economics provides a sustainable and ethical alternative to conventional economic systems. The proposed Islamic economic framework emphasizes distributive justice, inclusive economic participation, and responsible resource management. The research highlights how these principles can be applied in modern contexts, addressing challenges and ensuring alignment with sharia principles. Conclusion. The study concludes that the Islamic economic framework offers a viable and ethical alternative to conventional economic models, promoting fairness and social welfare. It also suggests several recommendations for integrating these principles into national economic policies to ensure more effective implementation.